2006
DOI: 10.1128/iai.74.5.3016-3020.2006
|View full text |Cite
|
Sign up to set email alerts
|

Bgp, a Secreted Glycosaminoglycan-Binding Protein of Borrelia burgdorferi Strain N40, Displays Nucleosidase Activity and Is Not Essential for Infection of Immunodeficient Mice

Abstract: Bgp, one of the surface-localized glycosaminoglycan-binding proteins of the Lyme disease spirochete, Borrelia burgdorferi, exhibited nucleosidase activity. Infection of SCID mice with B. burgdorferi strain N40 mutants harboring a targeted insertion in bgp and apparently retaining all endogenous plasmids revealed that Bgp is not essential for colonization of immunocompromised mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
64
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 57 publications
1
64
0
Order By: Relevance
“…The pathogen has a strong affinity for a diverse array of host extracellular matrix (ECM) components, including fibronectin, integrins, collagen, proteoglycans, and laminin (3,7,8,10,20,39,46). The host ECM likely provides a protective niche for B. burgdorferi, allowing the spirochete to persist in the host despite humoral and cellular immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogen has a strong affinity for a diverse array of host extracellular matrix (ECM) components, including fibronectin, integrins, collagen, proteoglycans, and laminin (3,7,8,10,20,39,46). The host ECM likely provides a protective niche for B. burgdorferi, allowing the spirochete to persist in the host despite humoral and cellular immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…Parveen et al reported that Bgp is not required for infection of immunodeficient mice (23), although it remains to be addressed whether the adhesin significantly contributes to infectivity in immunodeficient hosts and whether it is essential for infection of immunocompetent mice. Seshu et al showed that a BBK32 deficiency increases the ID 50 value by approximately 10-fold in immunocompetent mice (32), virtually consistent with a subsequent study by Li et al indicating that the BBK32 gene is not essential for the life cycle of B. burgdorferi either in the tick vector or the murine host (21).…”
mentioning
confidence: 99%
“…This may therefore translate into a lack of attenuation of infectivity following short-or long-term infection. Inactivation of proteins in B. burgdorferi that serve as adhesins, such as BBK32 (38,61) and Bgp (49), has resulted in either partial or no attenuation of infectivity, suggesting the role of multiple borrelial determinants in initiation and maintenance of infection. Hence, it is interesting to speculate that infectivity analysis of a BBA64/ BBA65/BBA66-negative triple mt will help further characterize the role of a subset of pgf 54 family members in the colonization and dissemination of B. burgdorferi within the mammalian host.…”
mentioning
confidence: 99%